2022
DOI: 10.1109/oajpe.2022.3208835
|View full text |Cite
|
Sign up to set email alerts
|

Long Duration Flexibility Planning Challenges and Solutions for Power System With Ultra High Share of Renewable Energy

Abstract: The uncertainty of wind/photovoltaics (PV) power generation and load fluctuations highlight the urgent need for flexible yet stable power resources. With the increasing in the share of renewable energy, the fluctuation presents a trend toward the longer periods, larger amplitudes, and more drastic changes. Therefore, research on the long duration flexible resource planning for the scenarios of the ultra high share of renewable power system (UHRPS) has become the focus. In this work, the main structural and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Then, only existing units are allowed to be online with (37). Lastly, the capacity sizing of ESS is defined in (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, only existing units are allowed to be online with (37). Lastly, the capacity sizing of ESS is defined in (38).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, hydro usually presents limitations regarding the amount of energy that can be produced over a given period. This limitation is usually related to regulations or strategies regarding the reservoir water level [38].…”
Section: Flexible Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that temporal aggregation or time slices, deployed in many previous studies, may not capture fundamental relationships, understate the value of broad technology portfolios, and do not solve time-based mismatch issues [18]. These studies, as well as others reported in [16,19,20], discussed chronological simulation as necessary to capture the challenges of long-term energy deficits due to seasonal variability.…”
Section: Global and Regional Developments And Studies-literature Reviewmentioning
confidence: 99%
“…In order to achieve the green and low-carbon transformation of China's power system, it is necessary to build the structural form and balancing mechanism of the new power system by building energy storage devices and transforming thermal power with flexibility starting from the planning stage [3][4][5][6]. The contradiction between the gradual increase in the flexibility demand of the new type of power sys-tem and the gradual decrease in the flexibility resources can be solved by reasonably optimizing the allocation of power supply and the installed proportion of thermal power and energy storage resources [7][8][9], and the planning concept will be shifted from the traditional balance of power to the balance of supply and demand of flexibility [10], which minimizes the planning cost and improves the capacity of new energy consumption from the economic point of view [11,12]. Reference [13] proposed a power supply expansion planning model considering unit commitment constraints for the problem of power system flexibility demand, optimizing investment decisions for variable renewable energy, energy storage systems and thermal power, and providing real-time flexibility using energy storage.…”
Section: Introductionmentioning
confidence: 99%